Digitisation, internationalisation, and changing business models in local media markets: an analysis of commercial media's perceptions on challenges ahead. Issue 2 (3rd April 2018) - Donders, Karen; Enli, Gunn; Raats, Tim; Syvertsen, Trine
ABSTRACT: Most research on the changes affecting commercial media focuses on big markets and, except in some instances, fails to incorporate media managers' views. By investigating perceptions of private media managers in two small markets, this article fills that void. It analyses how mainly legacy media managers view the impact of market and societal dynamics such as digitisation, internationalisation, and changing business models, and discusses the strategies and priorities they envisage to handle current challenges. Data collection rests on 20 expert interviews with high-level management in Flanders and Norway. The analysis builds on the main challenges identified in the literature, with a focus on the robustness versus fragility of small media markets. The main finding is that respondents do not go along with a doom scenario of their market, recognising though that the extent to which their companies and media ecosystems used to be shielded away from international trends and competition is over. Connecting with audiences is considered to be of pivotal importance in developing new business models.